Germline mutations in the new E1' cryptic exon of the VHL gene in patients with tumours of von Hippel-Lindau disease spectrum or with paraganglioma. Issue 11 (29th January 2020) - Buffet, Alexandre; Calsina, Bruna; Flores, Shahida; Giraud, Sophie; Lenglet, Marion; Romanet, Pauline; Deflorenne, Elisa; Aller, Javier; Bourdeau, Isabelle; Bressac-de Paillerets, Brigitte; Calatayud, María; Dehais, Caroline; et al.
Abstract : Backgrounds: The incidence of germline mutations in the newly discovered cryptic exon (E1') of VHL gene in patients with von Hippel-Lindau (VHL) disease and in patients with paraganglioma or pheochromocytoma (PPGL) is not currently known. Methods: We studied a large international multicentre cohort of 1167 patients with a previous negative genetic testing. Germline DNA from 75 patients with a single tumour of the VHL spectrum ('Single VHL tumour' cohort), 70 patients with multiple tumours of the VHL spectrum ('Multiple VHL tumours' cohort), 76 patients with a VHL disease as described in the literature ('VHL-like' cohort) and 946 patients with a PPGL were screened for E1' genetic variants. Results: Six different genetic variants in E1' were detected in 12 patients. Two were classified as pathogenic, 3 as variants of unknown significance and 1 as benign. The rs139622356 was found in seven unrelated patients but described in only 16 patients out of the 31 390 of the Genome Aggregation Database (p<0.0001) suggesting that this variant might be either a recurrent mutation or a modifier mutation conferring a risk for the development of tumours and cancers of the VHL spectrum. Conclusions: VHL E1' cryptic exon mutations contribute to 1.32% (1/76) of 'VHL-like' cohort and to 0.11% (1/946) of PPGL cohort and should be screened in patients with clinical suspicion of VHL, and added to panels for Next Generation Sequencing (NGS) diagnostic testing of hereditary PPGL. Our data highlight the importance of studying variants identified in deep intronic sequences, which would have been missed by examining only coding sequences of genes/exomes. These variants will likely be more frequently detected and studied with the upcoming implementation of whole-genome sequencing into clinical practice.